Pyrazine-based donor tectons: synthesis, self-assembly and characterization. Issue 11 (22nd January 2016) - Bhowmick, Sourav; Chakraborty, Sourav; Marri, Subba R.; Behera, J. N.; Das, Neeladri
Abstract : Two donor tectons, each bearing a central pyrazine moiety covalently linked to two pyridine units, have been self-assembled with PtII2 acceptor units to yield ionic nanoscalar metallamacrocycles, having a convex hexagonal cavity. Abstract : Two new supramolecular building blocks derived from pyrazine are introduced. These molecules, having pendant pyridine units covalently linked to central pyrazine ring, are structurally rigid with pre-defined bite angles. Therefore they can act as donor tectons in design of supramolecular hexagons using coordination driven self-assembly protocol. Multinuclear NMR (including 1 H DOSY) and mass spectrometry have been utilized to confirm the purity and stoichiometry of these self assembled hexagonal ensembles. PM6 molecular modeling studies corroborate their hexagonal shape and nanoscalar dimensions.